Use of the orthostatic board as a therapeutic resource: a systematic review (Research, Society and Development, 2020)
Background: Immobilism, characteristic in critical ICU patients, affects several organs and systems of the human organism, causing an extension of hospitalization and functional limitations that have repercussions for some time in the hospitalization period and after hospital discharge, affecting the quality and the reintegration of the individual into society. Physical therapy becomes important throughout this critical moment through preventive intervention that helps reduce the adverse effects of immobility. Objective: this article has as main objective to systematize the knowledge about the use of the orthostatic board in patients hospitalized in the ICU. Method: The research was conducted in the electronic databases: PubMed, SciELO, PEDro, CINAHL and MedLine, in a temporal cut from 2007 to 2019. We selected studies in Portuguese and English, related to the words quoted below. The descriptors used in the Portuguese language were: Early Mobilization, Orthotic Plaque, Orthostatic Board and Passive Orthostatism. In the English language, the descriptors were: early mobilization, orthostatic board, standing position, tilt table. Only randomized clinical trials were included in the treatment protocol in the intensive care setting, either in the control group or in the intervention group. Two researchers performed data collection independently, blindly and according to pre-established eligibility criteria. Results: The search for articles totaled 21,500 findings. The research was carried out from the peer reviews; and the readings of articles were made by their titles and summaries, and only six studies were considered. Conclusion: Although the studies evaluated showed positive functional outcomes regarding the use of the board for patient improvement, little evidence was found regarding the use of the technique within the ICU. Therefore, further studies are still needed in order to highlight the importance of using the board.